Transforming power dynamics through prefigurative public administration. Issue 3 (3rd July 2022) - Love, Jeannine M.; Stout, Margaret
Abstract: This is the introduction to a symposium which addresses the essential task of transforming power dynamics in public administration. The articles in this symposium each consider different sources of inspiration for resisting and disrupting systems of oppression while co-creating and sustaining counter-institutions that foster equity and justice. The authors look to social movements for instances of transformational praxis to inform the field of public administration.